2016
DOI: 10.1088/2043-6262/7/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanoparticles composed of silver and silver chloride for a plasmonic photocatalyst using an extract from a weed Solidago altissima (goldenrod)

Abstract: Phytosynthesis of nanomaterials is advantageous since it is economical, ecofriendly, and simple, and, what is more, in the synthetic protocols, nontoxic chemicals and biocompatible materials are used. Here, a green synthetic methodology of nanoparticles (NPs) composed of silver (Ag) and silver chloride (AgCl) NPs is developed using a leaf extract of Solidago altissima as a reducing agent for the first time. Utilization of a terrestrial weed for the synthesis of Ag and AgCl NPs is a novel environmentally friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 56 publications
6
48
0
Order By: Relevance
“…The formation of AgCl NPs might be attributed to the interaction of silver ions with chloride ions present in aqueous extract of Ecklonia cava . Similar results have been previously reported regarding the biosynthesis of AgNPs [ 75 , 78 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The formation of AgCl NPs might be attributed to the interaction of silver ions with chloride ions present in aqueous extract of Ecklonia cava . Similar results have been previously reported regarding the biosynthesis of AgNPs [ 75 , 78 ].…”
Section: Resultssupporting
confidence: 91%
“…It is in agreement with several studies that have reported similar XRD patterns of biosynthesized AgNPs [ 59 ]. It was found that other co-existing peaks at 2θ values of 28.0°, 32.5°, 46.4°, 55.1°, and 57.5° correspond to (1 1 1), (2 0 0), (2 2 0), (3 1 1), and (2 2 2) planes of face-centered cubic crystalline phase of silver chloride, respectively (JCPDS file: 31-1238) [ 75 , 76 , 77 , 78 , 79 , 80 ]. This result clearly indicates the production of Ag/AgCl composite nanoparticles (Ag/AgCl NPs) using aqueous extract of Ecklonia cava .…”
Section: Resultsmentioning
confidence: 99%
“…These findings confirm the semicrystalline nature of the silver nanoparticles. Additionally, there is very weak peak for AgCl at 2θ = 27.4 • for (200), which is reported by Kumar et al and Hamed et al as well [99,100]. The XRD analysis of the nanocompounds TCA-AgNPs-PI and Cinn-AgNPs-PI indicated both amorphous and crystalline regions [101].…”
Section: Discussionmentioning
confidence: 54%
“…Chlorine could have originated from the chlorine containing phytochemicals present in the persimmon byproducts. Several other studies have demonstrated chlorine in EDX spectra (Gou and others ; Kumar and others ). The average particle sizes of NPs determined by DLS were 120 nm for seed, 94 nm for peel and 118 nm for calyx.…”
Section: Resultsmentioning
confidence: 82%